2020
DOI: 10.1155/2020/3964973
|View full text |Cite
|
Sign up to set email alerts
|

Physical Frailty and Fall Risk in Community-Dwelling Older Adults: A Cross-Sectional Study

Abstract: Introduction. Frailty is a condition in older adults with decreased physical and cognitive performance that can affect health outcomes associated with fracture, disability, and falls. The aim of this study was to compare fall risk with different physical frailty statuses and investigate factors associated with fall risk in community-dwelling older adults. Methods. The population studied included 367 older adults (mean age = 73.2 years ± 7.0; 237 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…11 , 24 Some studies have used a variety of fall assessment tools. 12 , 13 These tools may be limited as they do not cover external factors that result in falls. 13 , 25 Therefore, this study focuses on fall awareness, falls, quality of life, and risk factors associated with falls among older adults from ethnic minority groups, including highlanders, hill-tribe settlers (Mien and Hmong), and lowlanders (Karens and Indigenous people).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 , 24 Some studies have used a variety of fall assessment tools. 12 , 13 These tools may be limited as they do not cover external factors that result in falls. 13 , 25 Therefore, this study focuses on fall awareness, falls, quality of life, and risk factors associated with falls among older adults from ethnic minority groups, including highlanders, hill-tribe settlers (Mien and Hmong), and lowlanders (Karens and Indigenous people).…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies have found that older adults who fall frequently experience physical injuries and a decline in their physical and mental health, leading to fear and a loss of confidence in performing daily activities. 12,13 Some studies suggest that an individual's awareness, positive attitude, and health concerns are important factors in preventing falls. 13,14 Quality of life is a term used in many fields and has a wide range of contexts depending on utility, health status, lifestyle, and satisfaction, 15 in addition, quality of life is related to the perception individuals have of their life expectancy in the context of the community and culture in which they live.…”
Section: Introductionmentioning
confidence: 99%
“…Varied approaches show a theoretical foundation for the medical and psychological management of the older adults that prioritizes their cultural identity, society, community, and family. [ 37 40 41 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Plain X-rays were the diagnostic imaging test ordered the most by general practitioners across all age categories before ultrasounds with a rate of 4.5 orders per 100 encounters and 2.7 orders per 100 encounters respectively [ 6 ]. These X-rays were mostly conducted for fall-related or skeletal issues and for acute bronchitis or bronchiolitis, conditions commonly experienced by the elder population [ 8 12 ]. This report demonstrates that easily transportable diagnostic imaging techniques, such as plain X-rays and ultrasounds, are still utilised abundantly and could represent a first step in delivering diagnostic technology at the place of residence.…”
Section: Introductionmentioning
confidence: 99%